Characteristics of nanopowders produced by wire electrical explosion oftinned copper conductor in argon; Materials Lettersэ; Vol. 62, № 17-18 - Kwon Y. -S.; Ilyin A. P. Aleksandr Petrovich; Tikhonov D. V. Dmitry Vladimirovich; Yablunovsky G. V.; An V. V. Vladimir Vilorievich (2008, 2008)
The end products of electrical explosion of copper wires coated with a thin tin layer were studied. Depositing tin (~ 1 wt.%) on the surface ofthe copper wire did not have a considerable effect on the relation between the sample dispersity and the input energy. When increasing the inputenergy, the tin content in surface and near-surface layers of the nanoparticles reduces sharply within 1.1–1.3 W/Ws. Decreasing the input energyincreases the oxidation onset temperature by ~ 20 °C when heating Cu (Sn) nanopowders unlike the copper nanopowders without additives. Themain phase in the powders is crystallized copper.